Socio Economic Caste Census 2011: Identification of BPL Persons - Joseph Abraham (KILA Journal of Local Governance, 2014)
The concepts and methodologies used at identifying the poor persons have undergone several changes in the past. While the National Sample Survey (NSSO) estimates provides the percentage of people below poverty line based on consumption expenditure specific caloric norms, the Below Poverty Line (BPL) surveys and the current Socio Economic Caste Census (SECC) 2011 helps in identifying the poor households by using a different set of concepts. The changes introduced at each round of BPL surveys to the currently on going SECC 2011 needs to be recapitulated for the purposes of administrative and policy needs. The introduction of country wide e- governances modules in the SECC2011 at identification of the poor are considered a major breakthrough and the results are awaited. To what extend the e- governance initiatives under taken in the realms of data collection, awareness generation and the involvement of Panchayati Raj Institutions (PRIs) and Grama Sabhas through a process of Claims and Objections Tracking Systems (COTS) by various states and union territories are helpful in arriving at the BPL list is a concern for all. As in the past but for decentralised efforts at data collection many errors are unlikely.